Research on health management technology of ship cabin equipment. Issue 1 (July 2021) - Zhuo, Jie; Wu, Maopu; Sun, Qingxin
Abstract: The research and development of health management technology of ship cabin equipment is backward, which can't meet the development needs of intelligent ship. In view of the current large number of ship cabin equipment and low operation and maintenance level, the study of cabin equipment system and reliability analysis are carried out with the cabin equipment as the research object, and the data of the cabin equipment are modeled by data collected and processed. The health management system of cabin equipment is developed to realize the functions of health management, such as equipment fault diagnosis and predictive maintenance, to improve the automation and intelligence level of equipment operation and maintenance.